Perbaikan Jalan Angkut Menggunakan Geotextile untuk Meningkatkan Produktivitas HD 785 pada Site Gurimbang Mine Operation, PT. Berau Coal: Improvement of Hauling Road with Geotextile to Increase Productivity of HD 785 at Site Gurimbang Mine Operation, PT. Berau Coal - Asof, Marwan; Purbasari, Diana; Agustian Putra, M. Andra (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2023)
PT. Berau Coal is one of the mining companies in Indonesia that focuses on coal mining and sales. This research was carried out on the haul road at Site Gurimbang Mine Operation, where the condition of the haul road is currently undulating and located above a swamp area. This condition reduces the speed of HD 785, resulting in the unit's productivity not achieving the company's target. The effort to improve the condition of the haul road is by using geotextile as a method of strengthening the haul road. The aim of this research is to determine the changes in soil density and soil bearing capacity after the geotextile reinforcement and to identify its impact on HD 785 productivity. The research was conducted by analyzing and processing data from the results of the DCP in-situ test to determine the soil density and soil bearing capacity in the initial and post-geotextile installation conditions. Actual field data collection in the form of HD 785 cycle time and speed data was used to evaluate the unit's productivity before and after geotextile installation. The results indicated that the utilizing geotextile can increase the soil density and soil bearing capacity to meet the CBR standards and soil bearing capacity for HD 785 units. The use of geotextile also increased the speed of HD 785 by 3 km/hour, both during load and empty travel, resulting in an increase in HD 785 productivity by 26% from the initial 43,821.63 bcm/month to 55,375.62 bcm/month.